Determining The Nutrition of Patient Based on Food Packaging Product Using Fuzzy C Means Algorithm - Sri Winiarti; Sri Kusumadewi; Izzati Muhimmah; Herman Yuliansyah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
The main idea in this research is the utilization of Fuzzy C Means (FCM) method as the determination of patient's nutritional status, which is implemented, in mobile application. Parameters used to cluster nutritional status are height, weight and age. The result of the decision will give 3 clusters on nutritional status is good nutrition, malnutrition and better nutrition. Mobile apps are used as a reminder of the nutritional value or ingredients contained in the packaging of food products while consuming food. The result of system testing for application of FCM algorithm in this mobile application obtained validation of 80%.